5-trialometil-4,5-diidro-1h-1-(carbonilpiridil)pirazóis: síntese e atividade biológica frente ao Mycobacterium tuberculosis - Navarini, Jussara (2008)
This work describes the synthesis of series of 5-hydroxy-3-[alkyl(aryl/heteroaryl)]-5-trifluoro[chloro]methyl-4,5-dihydro-1H-1(carbonylpyridyl)pyrazoles, obtained from the reactions of 1,1,1-trihalo-4-[alkyl(aryl/heteroaryl)]-4-alkoxy-3-alken-2-ones [CX3C(O)CH=CR1OR, where R = Me, Et; R1 = H, Ph, 4-ClPh, 4-BrPh, 4-FPh, 4-MePh, 2-Furyl, 2-Thienyl and X= F, Cl] with hidrazines (NH2NHC(O)Z), where Z = 4-pyridyl, 2-chloro-4-pyridyl and 3-pyridyl, in good yields (50-89%). The obtained compounds were evaluated for their in vitro biological activities against Mycobacterium tuberculosis ATCC 27294 (H37Rv) strains, where it was found that trifluoromethylated compounds were more active than their trichloromethylated analogues. Moreover, the position of the atom of nitrogen and the chloro substituent in the ring of pyridine influences the activity of these compounds. The synthesised pyrazoles with substituints R1= H and X=F (3a) and R1=4-MePh and X=F (3g) showed the best activity against the tested strains above mentioned. The compounds were characterized by analytical 1H and 13C NMR and of Mass Spectrometry (GC-MS), and its purities they were determined by Elementary analysis analysis.